(untitled) (Bangladesh Journal of Pharmacology, 2017)
The aim of this review is to report the medicinal plants which have anti- fibrotic effect characterized in different studies. They are summarized which include name of the plants, part used, liver fibrosis model, fraction of plant used and observations. The medicinal plants play an important role in treatment and prevention of liver fibrosis through different physiological mechanism. The effects of medicinal plant may delay the development of liver fibrosis and have potential to reverse or degrade the accumulation of extra cellular matrix. Four different databases are used and 18 plants are included which have the potential for reversal of liver fibrosis. There are also few more plants but they are not characterized well in literature.